Introduction to Psychology - Walinga, Jennifer; Open Textbook Library (Open Textbook Library, 2010)
This book is designed to help students organize their thinking about psychology at a conceptual level. The focus on behaviour and empiricism has produced a text that is better organized, has fewer chapters, and is somewhat shorter than many of the leading books. The beginning of each section includes learning objectives; throughout the body of each section are key terms in bold followed by their definitions in italics; key takeaways, and exercises and critical thinking activities end each section.
Chapter 1. Introducing Psychology -- Chapter 2. Introduction to Major Perspectives -- Chapter 3. Psychological Science -- Chapter 4. Brains, Bodies, and Behaviour -- Chapter 5. Sensing and Perceiving -- Chapter 6. States of Consciousness -- Chapter 7. Growing and Developing -- Chapter 8. Learning -- Chapter 9. Remembering and Judging -- Chapter 10. Intelligence and Language -- Chapter 11. Emotions and Motivations -- Chapter 12. Personality -- Chapter 13. Defining Psychological Disorders -- Chapter 14. Treating Psychological Disorders -- Chapter 15. Psychology in Our Social Lives -- Chapter 16. Stress, Health, and Coping
In English.
Description based on print resource
Keywords: Social sciences -- Textbooks; Psychology -- Textbooks